2009
DOI: 10.1002/jor.21013
|View full text |Cite
|
Sign up to set email alerts
|

Titanium uptake, induction of RANK‐L expression, and enhanced proliferation of human T‐lymphocytes

Abstract: There is increasing evidence that titanium ions are released from orthopedic implants by biocorrosion. The aim of this study was to investigate titanium uptake by human T-lymphocytes and its effects on phenotype and proliferation. Freshly isolated human nonadherent peripheral blood mononuclear cells (NA-PBMC), were exposed to TiCl 4 [Ti(IV)]. Bioavailability and distribution of Ti(IV) in T-lymphocytes was determined by energy-filtered electron microscopy (EFTEM). The effects of Ti(IV) challenge on nonactivated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
43
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 34 publications
3
43
0
Order By: Relevance
“…Using an autologous in vitro model, we have previously shown that Ti (IV) is taken up by dendritic cells and T-lymphocytes (24,50). This study further demonstrates that these Ti (IV) treated mDC can induce the generation of Ti (IV)-specific T lymphocytes.…”
Section: Fig 3 -Proliferation Of Ti (Iv)-specific T-lymphocytes Exposupporting
confidence: 62%
“…Using an autologous in vitro model, we have previously shown that Ti (IV) is taken up by dendritic cells and T-lymphocytes (24,50). This study further demonstrates that these Ti (IV) treated mDC can induce the generation of Ti (IV)-specific T lymphocytes.…”
Section: Fig 3 -Proliferation Of Ti (Iv)-specific T-lymphocytes Exposupporting
confidence: 62%
“…Previous work has recorded the immunogenic effect on the participation of the products of titanium corrosion in amplifying host inflammatory response and enhancing bone loss in peri‐implantitis lesions by means of an increased release of proinflammatory cytokines, 15 TNF‐α, 11 IL‐1β, 14 and RANKL 17 by host cells in the presence of titanium products. Nonetheless, the present work unveiled a previously unexplored association between bacterial plaque, dissolved titanium released into the peri‐implant tissues and peri‐implantitis.…”
Section: Discussionmentioning
confidence: 99%
“…Mice immune cells stimulated by lipopolysaccharide (LPS) in the presence of titanium ions show increased release of proinflammatory cytokines involved in bone resorption 15 . In addition, titanium particles have been shown to induce release of tumor necrosis factor (TNF)‐α when phagocytized by macrophages, 16 increase release of interleukin (IL)‐1β by macrophages, 14 and induce secretion of receptor activator of nuclear factor‐kappa B ligand (RANKL) upon entering T‐cells 17 stimulating bone resorption. This indicates corrosion as a potential etiologic factor in the pathogenesis of peri‐implantitis.…”
mentioning
confidence: 99%
“…The pathophysiological mechanism of AL is thought to be a sustained chronic inflammatory response that leads to an increase in osteolytic activity and loss of periprosthetic bone 12. Besides the role of wear debris in the initiation and development of AL, several groups have demonstrated the numerous effects that metal ions have on bone metabolism and potentially on implant failure 9, 13. Released metal ions appear to act directly on bone cells and are independent of the particulate phagocytosis/inflammation‐mediated pathways 9, 13.…”
Section: Discussionmentioning
confidence: 99%
“…The same studies have shown that Co 2+ and Cr 3+ ions enhance the expression of RANKL and osteoprotegerin by osteoblasts, thus enhancing osteoclastogenesis, and finally osteolysis 15. In addition, metal ions (e.g., Co, Cr, Mo, and Ti) induce elevated secretion of proinflammatory cytokines, including interleukin (IL)‐1α/β, IL‐6, and tumor necrosis factor (TNF)‐α 13, 16. TNF‐α acts directly on OC precursors, whereas IL‐6 and IL‐1α/β act indirectly by increasing the expression of RANKL and M‐CSF by osteoblasts, which in turn directly drive osteoclastogenesis 13.…”
Section: Discussionmentioning
confidence: 99%